Structural, vibrational, optical, photoluminescence, thermal, dielectric, and mechanical studies on zinc (tris) thiourea sulfate single crystal: A noticeable effect of organic dye *Project supported by the Fund from the Deanship of Scientific Research at King Khalid University, Saudi Arabia (Grant No. R.G.P.2/9/38). (May 2018) - Shkir, Mohd; Ganesh, V; AlFaify, S; S Yahia, I; Anis, Mohd
Abstract : In this work, uranine-dyed zinc (tris) thiourea sulfate (ZTS) monocrystals, 26 mm×15 mm×10 mm in size, were synthesized by the solution method at ambient temperature. Their purity, crystallinity, lattice parameters, and functional modes were studied by x-ray diffraction, Fourier transform-infrared spectroscopy (FT-IR), and FT-Raman spectroscopy analyses. The sodium ion content of the crystals from the dye was confirmed by elemental analysis. The diffused reflectance spectral analysis of the dyed crystal revealed a characteristic absorption band at 490 nm attributed to the presence of the dye. The calculated band gaps of the non-dyed and dyed crystals were 4.53 and 4.57 eV, respectively. A green emission peak at ∼ ( 512 ± 4 ) nm was observed in the photoluminescence spectrum of the uranine-dyed crystals. A differential scanning calorimetry study confirmed that the thermal stability improved owing to the addition of the dye. Dielectric and microhardness studies were conducted to examine the significant improvements in the corresponding properties of dyed crystals. The results demonstrated the competency of the dyed ZTS crystals for applications in optoelectronic devices.